Pemanfaatan Software Jurnal.id dalam Menunjang Efesiensi Pembuatan Laporan Keuangan di Prima Accounting - Intan Arum Aprelia; Putri Dwi Aprilia Nur Khasanah (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the extent to which the use of the accounting software Jurnal.id can enhance efficiency in the preparation of financial statements at Prima Accounting. Specifically, the research seeks to examine how the software facilitates the reporting process and to identify the various challenges encountered by users in its implementation. This study employs a qualitative method with a descriptive approach, aiming to present a factual and systematic depiction of Jurnal.id application within Prima Accounting. Data were collected through unstructured interviews with ten employees of Prima Accounting. The findings indicate that the implementation of Jurnal.id has significantly improved the recording and processing of financial transactions. As a web-based system, Jurnal.id provides automated features that enhance the speed and accuracy of financial reporting, thereby supporting more efficient decision making processes. However, some challenges remain, particularly regarding users’ initial understanding of the system and the need for adequate training. Overall, Jurnal.id has proven to be an effective digital accounting tool in improving operational efficiency and reporting accuracy within the organization.